Failure analysis of self-healing epoxy resins using microencapsulated 5E2N and carbon nanotubes. (22nd December 2020) - Zamal, Hasna Hena; Barba, David; Aïssa, Brahim; Haddad, Emile; Rosei, Federico
Abstract: Investigation on self-healing properties of epoxy containing microcapsules of pure 5-ethylidene-2-norbornene (5E2N) and mixed multi-walled carbon nanotube (MWCNT) suspension is presented in this work using lap shear and mode I fracture tests. While both systems show significant self-healing functionalities between 39% and 97%, those repaired with MWCNT/5E2N microcapsules are found to have mechanical recovery efficiencies two times higher than those containing 5E2N alone, under different types of loading. MWCNT/5E2N microcapsules are also found to improve the physical strength of the epoxy matrix much higher than microcapsules containing only 5E2N. Compared to self-healing epoxy systems made of 5E2N microvessels, the dispersion of 0.10 wt.% of only MWCNTs inside the encapsulated monomer increases the lap shear strengths of the pristine materials and the self-healing materials tested after one fracture/curing cycle, by about 50% and 250%, respectively. Using fractographic observations, Raman spectroscopy and scanning electron microscopy, we observe the occurrence of a ring opening metathesis polymerization reaction and the contribution of MWCNTs to strengthening the material. The present work indicates that the MWCNT/5E2N microcapsule when incorporated into an appropriate epoxy formulation can serve as efficient self-healing matrix material for laminated composites, as well as self-healing structural adhesives for composite bonded joints, two features that make this system highly relevant for applications in aerospace engineering.